Penapisan Senyawa Antimalaria yang Berasal dari Tumbuhan - SYAMSUDIN SYAMSUDIN (JURNAL ILMU KEFARMASIAN INDONESIA, 2008)
Efforts to discover and develop new antimalarial drugs have increased dramatically in recent years mainly because of the parasites’ resistance to existing antimalarial drugs. Selection of drug candidates for clinical trials in man and the design of clinical protocols are based upon consideration of data from a battery of preclinical test systems. All compounds are assessed initially in one or more primary models. A compound which is considered active by well established criteria in primary screening test is considered for further evaluation in successively more rigorous clinical test. At the end of each stage of testing, a decision is taken to advance the compound to the next stage or to discontinue it. Primary screening tests should have optimal sensitivity, a high degree of reproducibility, high throughput, should require a minimum quantity of test compound and bear low cost. As there is growing need for newer and more efficacious antimalarial drugs escpecially in tropical countries, more sensitive and economical screening models are needed. This review is an update of various conventional and latest in vitro and in vivo screening methods being used for evaluation of antimalarial compounds.